Candida auris: Epidemiology, risk factors, virulence, resistance, and therapeutic options - de Cássia Orlandi Sardi, Janaina; Silva, Diego Romário; Soares Mendes-Giannini, Maria José [UNESP]; Rosalen, Pedro Luiz (Elsevier, 2018)
Candida auris emerged as a pathogen resistant to multiple antifungal and has been associated with nosocomial outbreaks with high transmission capacity between hospitalized individuals. C. auris was first described in 2009, after being isolated from the external ear canal discharge of a patient in Japan. The difficulty in identification, incorrect use of antifungal drugs, and treatment failure are causes of high mortality. Since then, C. auris has been increasingly reported from East Asia to North America, with substantial fatalities and misidentification. This review aims at describing the epidemiology, virulence, risk factors, resistance, and therapeutic options in C. auris infections.
Keywords: Candida auris; Resistance; Virulence factor